2013
DOI: 10.1007/s12010-012-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Based Biologically Active Compounds: Synthesis, Characterization, DNA Interaction, Antibacterial, Cytotoxic and SOD Mimic Activities

Abstract: The square pyramidal copper(II) complexes of N, O- donor ligand and ciprofloxacin have been synthesized. Synthesized complexes were characterized by physicochemical parameters like elemental analysis, electronic, FT-IR and LC-MS spectra. The complexes were screened for their antimicrobial activity against Gram(+Ve), i.e. Staphylococcus aureus, Bacillus subtilis, and Gram(-Ve), i.e. Serratia marcescens, Pseudomonas aeruginosa and Escherichia coli, microorganisms in terms of minimum inhibitory concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
2
20
0
1
Order By: Relevance
“…The peak at 1593 cm À1 is ascribed to the C@N breathing vibration of the quinoline group, which is shifted towards lower frequencies of 1599 and 1598 cm À1 , respectively in complexes 1 and 2. Some new brands with medium to weak intensities appear in the region 498-530 cm À1 , which are assigned to Cu-N stretching vibrations [31]. This fact is agreement with the results determined by X-ray diffraction.…”
Section: Uv-vis and Ir Spectroscopy Of Complexes 1 Andsupporting
confidence: 90%
“…The peak at 1593 cm À1 is ascribed to the C@N breathing vibration of the quinoline group, which is shifted towards lower frequencies of 1599 and 1598 cm À1 , respectively in complexes 1 and 2. Some new brands with medium to weak intensities appear in the region 498-530 cm À1 , which are assigned to Cu-N stretching vibrations [31]. This fact is agreement with the results determined by X-ray diffraction.…”
Section: Uv-vis and Ir Spectroscopy Of Complexes 1 Andsupporting
confidence: 90%
“…Many drugs possess modified toxicological and pharmacological properties in the form of metal complex and probably Schiff bases are versatile C=N (imine) containing compounds possessing broad spectrum of biological activity and incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8]. In vivo studies have indicated that some biologically active compounds may become more carcinostatic and bacteriostatic upon chelation [9][10][11][12][13]. Such interaction with transition metal ions with amino acids, peptides and nucleic acids, are of immense biological importance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination sites are two azomethine nitrogens of the hydrazone moiety and two carbonyl groups of amidic moiety; each two donors chelated one metal ion. The shift of υ(C=N) to 1542 cm −1 and υ(C=O) amidic to 1644 in the Pd(II) complex and to 1552 and 1676 in the Ni(II) complex together with appearance of υ(M–N) [22] and υ(M–O) bands at ~465 and ~540 cm −1 , respectively. In the Ni(II) complex, the band of carbonyl groups splitted to two at 1697 and 1676 cm −1 ; the first is due to ketonic group which is not participated in bonding.…”
Section: Resultsmentioning
confidence: 99%